Concrete crack repairing material and preparation method thereof
By using concrete crack repair materials combined with modified nanozeolite particles and moisture-curable polysiloxane solution, the problem of insufficient repair ability of traditional materials in humidity environments is solved, and efficient crack filling and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411733249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional concrete restoration materials lack humidity responsiveness in humidity environments, making them difficult to effectively repair cracks, and lack of corrosion resistance, resulting in continuous damage to the concrete structure in humid environments.
A concrete crack repair material that combines modified nanozeolite particles and a moisture-curable hydroxyl-containing polysiloxane solution is prepared by ultrasonic dispersion and constant temperature stirring to form a composite material with humidity responsiveness.
The material can automatically absorb water and solidify in a humid environment, forming a three-dimensional nanopackaging structure, filling cracks, and releasing nanoparticles by absorbing moisture, further filling the micropores inside the cracks, improving the compressive strength and corrosion resistance of the concrete structure.
Smart Images

Figure CN119551928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a concrete crack repairing material and a preparation method thereof, and belongs to the technical field of building materials. Background Art
[0002] Concrete is a widely used structural material in construction projects. However, during long-term service, concrete structures are often prone to crack damage due to various external environmental conditions, which in turn leads to a decline in performance and affects the appearance. Crack damage in concrete not only weakens the mechanical properties of its structure, but also provides a channel for the entry of corrosive media (such as water, sulfate ions, chloride ions, etc.), accelerating the damage and deterioration of concrete. Especially in marine environments, underground facilities and industrial buildings, concrete structures exposed to these media face serious durability problems. Therefore, the development of effective concrete crack repair materials has always been a hot research topic in the field of building materials.
[0003] At present, traditional concrete crack repair methods mainly include physical blocking and chemical repair methods, such as coating protection, grouting repair, etc. However, these methods usually have certain limitations: the repair operation is complicated, the material durability is poor, and it is difficult to effectively repair microcracks. More importantly, traditional concrete repair materials basically do not have humidity response characteristics, and the crack repair effect in a humid environment is not obvious enough. In particular, the repair materials often have difficulty in performing their repair functions and lack of anti-corrosion ability in a humidity erosion environment, resulting in continuous expansion of concrete cracks and concrete deterioration. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In order to solve the problems of the lack of humidity responsiveness of traditional concrete repair materials, low crack repair ability in a humidity environment, insufficient corrosion resistance, etc., the present invention provides a concrete crack repair material and a preparation method thereof.
[0006] (II) Technical solution
[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0008] A concrete crack repairing material comprises modified nanoparticles and a polysiloxane organic solution, wherein the modified nanoparticles are modified nano zeolite particles, and the polysiloxane organic solution is a moisture-curable hydroxyl-containing polysiloxane solution.
[0009] In the concrete crack repairing material as described above, preferably, the particle size of the nano zeolite particles is 50nm to 200nm.
[0010] Furthermore, the modified nano-zeolite particles are nano-zeolite particles modified with a silane coupling agent; the silane coupling agent is a 3-aminopropyltriethoxysilane solution (KH-550 solution), and its mass fraction is 1.5-3%.
[0011] In the concrete crack repair material as described above, preferably, the moisture-curable hydroxyl-containing polysiloxane solution is a deoxime-type RTV silica gel solution or a dealcohol-type RTV silica gel solution with a mass concentration of 10 to 30%.
[0012] In the concrete crack repairing material as described above, preferably, the mass ratio of the modified nano zeolite particles to the moisture-curable hydroxyl-containing polysiloxane solution is 1:10 to 1:15.
[0013] The preparation method of the concrete crack repair material as described above comprises the following steps: S1, mixing the silane coupling agent with the nano zeolite particles, and then ultrasonically dispersing the silane coupling agent so that the silane coupling agent is evenly attached to the surface of the nano zeolite particles, mixing and stirring the dispersed mixture at a constant temperature, and then drying the mixture to obtain modified nano zeolite particles;
[0014] S2. Mixing the modified nano-zeolite particles with the polysiloxane organic solution, stirring and mixing until uniform, and then ultrasonically treating the mixture to obtain a concrete crack repair material.
[0015] In the preparation method as described above, preferably, in step S1, the silane coupling agent is a 3-aminopropyltriethoxysilane solution with a mass fraction of 1.5-3%, and the nano zeolite particles and the silane coupling agent are added in a mass ratio of 1:5-1:15.
[0016] In the preparation method as described above, preferably, in step S1, the ultrasonic conditions are as follows: the power is 300 W, the ultrasonic time is 10 to 30 min; the set temperature of the constant temperature mixing and stirring is 80°C, the stirring speed is 300 to 500 rpm, and the stirring time is 20 to 30 min; the drying conditions are 80°C and the time is 2 to 4 hours.
[0017] In the preparation method as described above, preferably, in step S2, the polysiloxane organic solution is a deoxime type RTV silica gel solution or a dealcohol type RTV silica gel solution with a mass concentration of 10 to 30%.
[0018] The mass ratio of the modified nano zeolite particles to the polysiloxane organic solution is 1:10 to 1:15.
[0019] In a preferred embodiment, in step S2, the stirring rate is 500-1500 rpm, and the stirring time is 10-20 min; the power of ultrasonic treatment is 300 W, and the ultrasonic time is 10-20 min.
[0020] When in use, the concrete crack repair material obtained by the above preparation method is added to the concrete cracks to achieve the effect of modifying the cracks.
[0021] (III) Beneficial effects
[0022] The beneficial effects of the present invention are:
[0023] The concrete crack repair material provided by the present invention has humidity responsiveness. When the concrete cracks injected with the repair material are exposed to a humid environment, it can automatically absorb moisture and solidify to form a three-dimensional nano-encapsulation structure to fill the cracks. After continuing to absorb moisture and swell, it can not only release the encapsulated nanoparticles to the outside, but also further fill the micropores inside the cracks, thereby being able to quickly fill the gaps in the cracks and improve the compressive strength of the concrete structure, thereby solving the problems of the lack of humidity responsiveness of traditional concrete repair materials and the low crack repair ability in a humid environment.
[0024] The concrete crack repair material provided by the present invention can release the modified nano zeolite particles wrapped inside after absorbing moisture and swelling, thereby adsorbing and fixing anions (such as sulfate ions and chloride ions) in a humid environment, and can be easily applied in the research field of improving the corrosion resistance of concrete.
[0025] In addition, the preparation method of the concrete crack repair material provided by the present invention has a relatively simple process, is easy to operate, has high adaptability at the construction site, can realize automated crack repair, reduces the unnecessary costs caused by frequent maintenance in the later stage, and improves the durability and economy of the project. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The flowchart of the preparation of modified nano zeolite particles in step (1) of Example 1 or 2;
[0027] Figure 2 This is a flow chart for preparing the humidity-responsive composite material in step (2) of Example 1 or 2. DETAILED DESCRIPTION
[0028] The concrete crack repair material provided by the present invention adopts moisture-curable hydroxyl-containing polysiloxane (such as moisture-curable silica gel RTV after introducing hydroxyl groups) as a liquid organic carrier to carry modified nano zeolite particles. The prepared composite material will undergo moisture absorption and curing when encountering moisture invasion. The surface drying time of moisture absorption and curing is controlled within 5 to 40 minutes. After curing, a dense three-dimensional network structure is formed to wrap the nano zeolite particles and fill the concrete cracks.
[0029] The concrete crack repair material provided by the present invention has a preparation method comprising: S1, using nano zeolite particles as nano materials, and subjecting them to modification treatment with a silane coupling agent to obtain modified nano zeolite particles, so as to enhance their compatibility with polysiloxane solutions and have the ability to adsorb and fix negative ions (such as sulfate ions and chloride ions); S2, the liquid organic matter selected is a moisture-curable hydroxyl-containing polysiloxane (such as moisture-curable silica gel RTV introduced with hydroxyl groups), and the concentration range thereof is set to 10% to 30% (mass fraction);
[0030] The modified nano-zeolite particles are added to a liquid organic solvent of a moisture-curable hydroxyl-containing polysiloxane, mixed and stirred for 10 to 20 minutes, and then treated with an ultrasonic disperser for 10 to 20 minutes to make it into a suspension state to ensure that the nano-particles are evenly distributed in the composite material before and after curing, and finally a composite material of polysiloxane carrying modified nano-zeolite particles with humidity responsiveness is obtained.
[0031] Among them, the modified nano zeolite particles are prepared by mixing nano zeolite particles having a porous structure and a high specific surface area with a silane coupling agent solution having a mass fraction of 1.5 to 3%, and then ultrasonically dispersed for 10 to 30 minutes to ensure that the modifier is evenly attached to the surface of the nano zeolite particles. After that, the dispersed mixture is stirred at a constant temperature, with a set temperature of 80° C., a stirring speed of 300 to 500 rpm, and stirring for 20 to 30 minutes. Finally, the nano zeolite is dried (drying temperature is 80° C., time is 2 to 4 hours), and finally the modified nano zeolite particles are obtained.
[0032] A large number of experimental studies have found that if the concentration of silane coupling agent is lower than 1.5%, it cannot fully cover the surface of the particles, resulting in a decrease in adsorption performance, while a concentration higher than 3% is prone to cause particle agglomeration, affecting the dispersion and uniformity of the particles; insufficient ultrasonic dispersion time in the modification stage (such as <10 minutes) will cause particle agglomeration and uneven attachment of the coupling agent, while too long a time (such as >30 minutes) may destroy the surface structure of the particles; when the temperature of constant temperature stirring is lower than 80°C, the modification of the nano zeolite by the coupling agent is incomplete and the activation of the nano zeolite surface is insufficient, while when the temperature is higher than 80°C, by-products may be produced, reducing the modification efficiency of the coupling agent; when the drying temperature is lower than 80°C, solvent residues (such as moisture, unreacted alcohols) may result, reducing the functionalization ability of the particle surface; and when it is higher than 80°C, it may cause overheating of the particle surface or decomposition of the coupling agent. In addition, insufficient drying time (such as <2 hours) will make the particle surface incompletely stable, while too long a time (such as >4 hours) may cause particle agglomeration and reduced activity. These problems will lead to a decrease in the material's adsorption performance, dispersibility and humidity responsiveness, seriously affecting the effect of crack repair.
[0033] When the mass concentration of the deoxime RTV silica gel solution or the dealcohol RTV silica gel solution is lower than 10%, the adhesion will be too low, the moisture absorption effect will be poor, the dispersion of the nanoparticles will be unstable, and the repair effect will be affected; when the concentration is higher than 30%, the solution viscosity will be high, the operating performance will be poor, the nanoparticles will be difficult to disperse, and the nanoparticles will agglomerate. Therefore, the mass concentration of the deoxime RTV silica gel solution or the dealcohol RTV silica gel solution is preferably 10 to 30%. If the ultrasonic treatment time during the mixing stage of the modified zeolite particles and the RTV silica gel solution is too short (such as <10 minutes), the modified nano zeolite particles will agglomerate and be unevenly dispersed in the mixed solution. The preferred time is 10 to 20 minutes, and no excessive treatment is required.
[0034] The material obtained by the above preparation method will form a three-dimensional nano-encapsulation structure after moisture absorption and curing. When the encapsulation structure continues to be invaded by moisture, it will first absorb moisture from the surface and become saturated until it absorbs moisture and swells. It can not only release the encapsulated nanoparticles to the outside, but also further fill the micropores inside the cracks, thereby improving the crack resistance of the concrete structure.
[0035] Among them, the modified nano zeolite particles in the present invention can adsorb sulfate and chloride ions. The high specific surface area and pore structure of the nano zeolite give the material a stronger adsorption capacity, and the modification further enhances its dispersibility and activity in complex systems; through the modification of the silane coupling agent, the dispersibility of the nano zeolite particles in the RTV silica gel solution is significantly improved, avoiding particle agglomeration, ensuring the uniform performance of the composite material, and enhancing its adhesion and mechanical properties after moisture curing; when the moisture or environment changes, the composite material gradually releases the nano zeolite particles therein to achieve its functional release in specific scenarios.
[0036] In the present invention, ultrasonic dispersion is used to achieve efficient dispersion of nanoparticles in the liquid phase, avoid agglomeration, ensure uniform particle distribution, improve the surface modification degree of nano-zeolite, and ensure the performance of the composite material. If ultrasonic dispersion is not performed during the modification stage of nano-zeolite particles, the nano-zeolite particles will agglomerate, resulting in reduced modification effect; in addition, modified particles that have not been ultrasonically dispersed are prone to form agglomerates in RTV silica gel, and the particles may also be stratified due to gravity sedimentation or viscosity differences, resulting in uneven performance of the composite material in terms of adsorption, mechanical properties, etc.
[0037] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0038] Example 1
[0039] (1) 50 g of a silane coupling agent with a mass fraction of 1.5%, wherein the silane coupling agent is 3-aminopropyltriethoxysilane (KH-550 solution) as a modifier, is mixed with 10 g of nano zeolite particles with a particle size of 100 nm, and ultrasonic dispersion is performed for 15 minutes at an ultrasonic power of 300 W, so that the silane coupling agent is uniformly attached to the surface of the nano zeolite particles. Then, the mixture is mixed and stirred at a constant temperature of 80° C. for 30 minutes at a stirring speed of 300 rpm, and finally dried at 80° C. for 2 hours to obtain modified nano zeolite particles. The operation process is as follows: Figure 1 shown.
[0040] (2) 10 g of the modified nano-zeolite particles were added to 100 g of a 10% polysiloxane liquid organic solvent (deoxime-type RTV silica gel solution, available from Momentive Chemical (China) Co., Ltd.), and stirred at 1000 rpm for 10 minutes. Subsequently, ultrasonic dispersion treatment was performed for 15 minutes using the same ultrasonic disperser with an ultrasonic power of 300 W to obtain a humidity-responsive composite material based on polysiloxane-carried modified nanoparticles. The operation process is as follows: Figure 2 shown.
[0041] Example 2
[0042] (1) 100 g of 2% by mass silane coupling agent, 3-aminopropyltriethoxysilane (KH-550 solution) as a modifier, and 10 g of nano zeolite particles with a particle size of 150 nm were mixed, and ultrasonic dispersion was performed for 30 minutes at an ultrasonic power of 300 W, so that the silane coupling agent was uniformly attached to the surface of the nano zeolite particles, and then the mixture was stirred at a constant temperature of 80° C. for 30 minutes at a stirring speed of 300 rpm, and finally dried at 80° C. for 2.5 hours to obtain modified nano zeolite particles;
[0043] (2) Add 10 g of the modified nanoparticles to 150 g of a 20% polysiloxane solution (i.e., a dealcoholized RTV silica gel solution, which can be purchased from Maitu Chemical (China) Co., Ltd.), stir at 1500 rpm for 20 minutes, and then use an ultrasonic disperser for 20 minutes to obtain a humidity-responsive composite material prepared based on polysiloxane-carried modified nanoparticles.
[0044] Comparative Example 1
[0045] Take 460g of cement and mix it with 175g of water, stir for 2min, and prepare a slurry repair material with the same water-cement ratio as the concrete structure to be repaired.
[0046] Comparative Example 2
[0047] (1) 100 g of a silane coupling agent with a mass fraction of 4%, i.e., 3-aminopropyltriethoxysilane (KH-550 solution) as a modifier, was mixed with 10 g of nano zeolite particles with a particle size of 200 nm, and ultrasonically dispersed for 15 minutes at an ultrasonic power of 300 W. Then, the mixture was stirred at a constant temperature of 80° C. for 30 minutes at a stirring speed of 300 rpm. Finally, the mixture was dried at 80° C. for 3 hours to obtain modified nano zeolite particles.
[0048] (2) 10 g of the modified nanoparticles were added to 200 g of a 35% polysiloxane solution (de-alcoholized RTV silica gel solution, available from Maitu Chemical (China) Co., Ltd.), stirred at 1500 rpm for 20 minutes, and then ultrasonically dispersed for 20 minutes using an ultrasonic disperser to obtain a humidity-responsive composite material based on polysiloxane-carried modified nanoparticles.
[0049] The humidity responsive composite materials prepared in the above Examples 1-2 and the concrete crack repair materials in Comparative Examples 1 and 2 were poured into a 100mm×100mm×100mm concrete structure with the same water-cement ratio and damaged cracks (artificial cracks with a width of 0.1-1mm, a length and a depth of no more than 65mm were made by the "embedded method"), and the concrete structure was placed in an environment with a humidity greater than 95% for curing for 3-7 days. Subsequently, ultrasonic waves were used to detect whether the repaired crack area of the concrete structure was repaired. The filling rate was indirectly estimated through ultrasonic characteristics such as sound velocity, signal strength, and energy attenuation, and its compressive strength was tested. Among them, crack filling rate = 100% × (V 修复后 -V 裂缝原始 )÷(V 基准 -V 裂缝原始 ), V 修复后 is the speed of sound in the repaired concrete crack area, V 裂缝原始 is the speed of sound in the concrete crack area before repair, V 基准 is the sound velocity in the normal area of concrete; the sound velocity is calculated with reference to CECS21:2000 "Technical Code for Ultrasonic Detection of Concrete Defects", and the compressive strength is obtained by testing with reference to "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB / T50081-2019. The test results are shown in Table 1.
[0050] Table 1 Test results
[0051]
[0052] As can be seen from Table 1, the existing pure slurry repair material with the same water-cement ratio used in Comparative Example 1 has a filling rate difference of more than 28% and a compressive strength difference of more than 10% compared with Examples 1 and 2 of the present invention, which is significant and the repair is not good. If the concentration of the silane coupling agent and polysiloxane solution used is too high, it will lead to agglomeration of nanoparticles and poor operating performance, which will affect the overall repair effect. It can be seen that the humidity-responsive composite material obtained by the preparation method of the present invention has a good filling effect on cracks, and can autonomously repair cracks in damaged concrete structures in a humidity environment, thereby improving the compressive strength of concrete structures.
[0053] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A concrete crack repair material, characterized in that: The invention comprises modified nanometer particles and polysiloxane organic solution, wherein the modified nanometer particles are modified nanometer zeolite particles, and the polysiloxane organic solution is a moisture-curable hydroxyl-containing polysiloxane solution.
2. The concrete crack repair material according to claim 1, characterized in that: The particle size of the nano zeolite particles is 50nm to 200nm.
3. The concrete crack repair material according to claim 2, characterized in that: The modified nano zeolite particles are nano zeolite particles modified by a silane coupling agent; the silane coupling agent is a 3-aminopropyltriethoxysilane solution, wherein the mass fraction of the 3-aminopropyltriethoxysilane is 1.5-3%.
4. The concrete crack repair material according to claim 1, characterized in that: The moisture-curable hydroxyl-containing polysiloxane solution is a deoxime-type RTV silica gel solution or a dealcohol-type RTV silica gel solution with a mass concentration of 10 to 30%.
5. The concrete crack repair material according to claim 1, characterized in that: The mass ratio of the modified nano zeolite particles to the moisture-curable hydroxyl-containing polysiloxane solution is 1:10 to 1:
15.
6. The method for preparing the concrete crack repairing material according to any one of claims 1 to 5, characterized in that: It includes the following steps: S1, after mixing the silane coupling agent and the nano zeolite particles, ultrasonically disperse them so that the silane coupling agent is evenly attached to the surface of the nano zeolite particles, mix and stir the dispersed mixture at a constant temperature, and then dry it to obtain modified nano zeolite particles; S2. Mixing the modified nano-zeolite particles with the polysiloxane organic solution, stirring and mixing until uniform, and then ultrasonically treating the mixture to obtain a concrete crack repair material.
7. The preparation method according to claim 6, characterized in that: In step S1, the silane coupling agent is a 3-aminopropyltriethoxysilane solution with a mass fraction of 1.5-3%, and the mass ratio of the nano zeolite particles to the silane coupling agent is 1:5-1:
15.
8. The preparation method according to claim 6, characterized in that: In step S1, the ultrasonic conditions are as follows: the power is 300W, the ultrasonic time is 10 to 30 minutes; the set temperature of the constant temperature mixing and stirring is 80°C, the stirring speed is 300 to 500rpm, and the stirring time is 20 to 30 minutes; the drying conditions are 80°C and the time is 2 to 4 hours.
9. The preparation method according to claim 6, characterized in that: In step S2, the polysiloxane organic solution is a deoxime type RTV silica gel solution or a dealcohol type RTV silica gel solution with a mass concentration of 10-30%; the mass ratio of the modified nano zeolite particles to the polysiloxane organic solution is 1:10-1:
15.
10. The preparation method according to claim 6, characterized in that: In step S2, the stirring rate is 500-1500 rpm, and the stirring time is 10-20 min; the power of ultrasonic treatment is 300 W, and the time is 10-20 min.